CHRONIC MYELOMONOCYTIC LEUKEMIA - REVIEW AND CLINICAL EXPERIENCE OF THE HEMATOLOGY DEPARTMENT UMHAT "ST. MARINA" - VARNA - Ilina Micheva; Trifon Chervenkov; Canka Ruseva; Liana Gercheva (Peytchinski Publishing, 2016)
Chronic myelomonocytic leukemia (CMML) is a rare de novo myeloid neoplasm that exhibits dysplastic and proliferative features at presentation. The diagnosis is problematic with several specific controversial issues. Aim: To analyze the cases with CMML diagnosed in the Hematology clinic, UMHAT "St. Marina", Varna with assessment of risk, prognosis and survival. Materials and methods: The results from cytology, flow cytometry, histology, and genetics are re-estimated. For the risk stratification the CPSS was used. The statistical analysis is performed using SPSS 19. Results: Fifteen patients with CMML, 12 men and 3 women, with median age of 69,8 years were included in the study. According to the leukocyte count 12 were myeloproliferative (CMML/MP) and 3 myelodysplastic CMML (CMML/MD). The flow cytometry of peripheral blood and bone marrow was characterized by CD14, CD64, CD16 and CD56 expression. According to the histology of the bone marrow 2 cases were described as MDS, 1 as MDS/MPN, the rest as MPN with fibrosis in two of the cases. The cytogenetic risk was high in 5 patients and low in 10. According to CPSS one patient was with low risk, 3 with intermediate 1, 9 with intermediate 2 and 2 with high risk. Acute myeloid leukemia transformation occurred in 9 patients within median period of 13.1 months. The median survival after transformation was 2,5 months. The median survival in the whole group was 21.4 months. Conclusion: CMML is an aggressive disease. The prognosis of patients with CMML is poor, with low survival and high risk of transformation. The therapeutic options are limited.